Futur des relations internationales ou relations internationales du futur? - Korany, Bahgat (Études internationales, 1984)
This last paper in the volume tries to pull the threads together and to detect trends of evolution in the analysis of international relations. The discussion is limited to three issues deemed basic to this evolution: 1) the increasing g importance of technology and its impact on the world System, and especially on one of its basic components: the nation-state ; 2) contents and characteristics of the new industry of futurology ; and 3) the rise of political economy as a basic approach to the study of international relations. It is suggested that we are growing beyond such simplistic divisions as "High" and "Low Politics", and obsession with methodologism per se, and that we are increasingly putting rigor and interdisciplinarity in the service of analysing "substantial" issues of international relations.